Kamus matematika analisis - Kerami, Djati; Pusat Pembinaan dan Pengembangan Bahasa (Jakarta : Pusat Pembinaan dan Pengembangan Bahasa, Departemen Pendidikan dan Kebudayaan, 1994)
Indonesian-English dictionary of mathematical analysis terms.
Indonesian and English.
Includes bibliographical references (p. 86).
Keywords: Mathematical analysis -- Dictionaries -- Indonesian; Indonesian language -- Dictionaries -- English; Mathematical analysis -- Dictionaries; English language -- Dictionaries -- Indonesian